6b+10=-2

Simple and best practice solution for 6b+10=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b+10=-2 equation:


6b+10=-2

We simplify the equation to the form, which is simple to understand
6b+10=-2

We move all terms containing b to the left and all other terms to the right.
+6b=-2-10

We simplify left and right side of the equation.
+6b=-12

We divide both sides of the equation by 6 to get b.
b=-2

See similar equations:

| 7x-3x^2=2 | | 7x-36=6x+3 | | 6y+6=18 | | -16x^2+80x=100 | | -4x+9=-39 | | b/1+6=2 | | -x+6=-21+8x | | u=3(5-u)+1 | | 4+6x=-62 | | 3(3x-4)=2x-8 | | 4t+3(2-t)=13 | | 2+7x=-5 | | -6(3x+6)+2= | | 3x+4=-5+2x | | -7x-8=-71 | | -7-2x=-9 | | (2t^2-t-6)(2t^2+2t-1)= | | 7(2y-3)=-16 | | -5+4x=35 | | 40+35=b | | 5n+8n= | | 64=-16x^2+80x | | 3-p-4+p= | | 3(4x+12)=48 | | 45+35c=b | | 1-5a+a-8= | | 1607-1531= | | 118=-16x^2+80x | | 5q-6=2(q+3) | | v+4v= | | -1(x-4)+2=6(x+3) | | 4x+11x=-2 |

Equations solver categories